Pengaruh teknik supercrowning terhadap kejadian ruptur perinemun pada primipara - Fransiska Surayniwaty; Yuni Kusmiyati; Asmar Yetty Zein (Jurnal Kesehatan Ibu dan Anak, 2013)
The Super crowning Technique is a term where "crowning" time was happened and extended for minimum a minute or until one or two uterine contractions appear. The function of this technique is allowing the vagina and perineum stretch slowly around fetus's head which start to emerge, so it will prevent the tear of perineum caused the head come out taster. When stretch is happening, hot sensation will be a signal to stop pushing. The point of this technique is to control the mother when fetus head on crowning position. This technique was not recommended for some obstetrics condition which is need faster delivery such as fetal distress. In 2012, 89,70% rupture of perineum was happened on primipara in dr. Soedarso Hospital. This study aimed for knowing the influence of super crowning technique to rupture of perineum in the second stage of labor on primipara in dr. Soedarso Hospital 2013. This study was an experiment as post-test with control group design. Sampling technique was Purposive Sampling as the subject is primigravida. The numbers of sample was 30 subjects, divided into two groups consist of 15 subjects as treatment group using super crowning method and 15 subjects as control group using APN standard method. The data analyzed by Chi-square test and Relatives Risk (RR). This study showed that rupture of perineum on super crowning technique was fewer than APN standard technique with p-value O,O3 and RR2,7 (CI 95% 1,12- 6,71). There is any correlation between super crowning technique to rupture of perineum on primipara. Super crowning technique as the protective factor to rupture of perineum.